Reestructuración técnico administrativa de la empresa Majaplast Ltda., ubicada en la ciudad de Bogotá, D.C. (2021)
This work was carried out in the company Majaplast Ltda., which is located in the city of Bogotá D.C., in order to carry out an administrative technical restructuring after an analysis of the current state of the company to solve the internal problems. A diagnosis based on the PESTAL tool was started to analyze the company's position in the face of eventualities at the national and local levels; the DOFA matrix was implemented, identifying strategies that the company must execute to reduce weaknesses, increase strengths, control threats, and seize opportunities. To continue, industrial engineering tools such as process diagrams, capacity calculation and analysis, time and movement analysis, ergonomics and anthropometry studies were applied; in order to increase the productivity of the company by reducing downtime and unnecessary displacements.